Evaluación funcional y estructural del puente vehicular Quebrada Rondán, ubicado en la carretera Quamote – Socavón kilómetro 7 + 000, del cantón Guamote, provincia de Chimborazo, y análisis de dos alternativas de diseño - Gusqui Bejarano, Caterine Elizabeth (2016)
This project includes THE FUNCTIONAL AND STRUCTURAL EVALUATION OF THE VEHICULAR BRIDGE “QUEBRADA RONDÁN”, LOCATED AT THE GUAMOTE-SOCAVÓN ROAD - KM 7 + 000, IN GUAMOTE CANTON, CHIMBORAZO PROVINCE, AND THE ANALYSIS OF TWO ALTERNATIVES OF DESIGN " for which, several field inspections, concrete test hammer, traffic count (AADT) and various structural analyzes were conducted, which are detailed in this product. For the functional and structural evaluation, the data of various pathologies present in the bridge were field collected, which were analyzed and weighted element by element thus obtaining the condition index of each element (ICE) and the bridge condition index (PCI), for which an adequate assessment methodology was established. In order to understand the problems of the bridge, design analysis of elements with greater involvement was made, for which we should do the redesign of external beams and supports thereby allowing compare the results obtained with specified in construction plans. Subsequently we analyzed the constructive methods used on the bridge, from the evidence present in the structure. Finally, in response to the current condition of the structure we propose the maintenance and structural reinforcement in it for which solutions to the various pathologies and two proposals for reinforcement the external beam is raised, which include the respective reference budget.